(untitled) (Research, Society and Development, 2022)
This work aimed to carry out an ethnobotanical survey of plants commercialized as medicinal and phytotherapics in the municipality of Resende, RJ. Therefore, the main types of commerce in medicinal plants and phytotherapics were mapped and the plant species commercialized in the municipality were registered. The traditional use reported was correlated with the biological properties of metabolites biosynthesized by plant species already described in the literature. The ethnobotanical survey and research on the use of plants species and phytotherapics in the city revealed that 44% of the species described in RENISUS are sold in the open-air market and herbal stores visited, and 77% of these species are among the most consumed. It was possible to observe that many of the biological properties for which plant species are traditionally consumed are correlated with biosynthesized metabolites and evidence described in the literature. These results can help implement the National Policy on Medicinal Plants and Phytotherapics in the municipality and in Sul Fluminense, in addition to contributing to safe access, rational and sustainable use of biodiversity.